Proximate composition, mineral content and amino acid profile of Irvingia gabonensis O’Rorke baill leaf - Ewere, Efosa; Etim, Oboso; Usunobun, Usunomena (International Journal of Scientific World, 2016)
Several plants are utilized for medicinal and nutritional purposes. Irvingia gabonensis O’Rorke Baill leaf is used in herbal medicine for treatment of a number of ailments. This study was therefore carried out to investigate the proximate composition, antinutritional factors, mineral composition and amino acid profile of Irvingia gabonensis O’Rorke Baill leaf. The proximate and antinutritional factors analyses were done using standard procedures. The mineral analyses were done using flame photometry, titrimetic method, molybdo vanadate method and atomic absorption spectrophotometry and the amino acid profile was done with the aid of Applied Biosystems PTH amino acid analyzer. Results of proximate analyses were carbohydrates (75.15±1.29 %), protein (11.43±1.07 %), fat (1.99±0.74 %), fibre (4.89±0.61 %), ash (6.71±0.28 %), moisture (5.12±0.03 %) and caloric value (364.30±5.95 Kcal). Antinutrients (phytate, oxalate and cyanide) levels in the leaf were also very low. Results from mineral analyses obtained revealed that the leaf is also a very rich source of calcium, potassium, sodium, magnesium and so on. Compared with the World health organization (WHO) standards, results of the amino acid profile showed that the leaf is very rich in isoleucine, leucine, lysine, phenylalanine, threonine, valine and tyrosine which are nutritionally essential amino acids. Furthermore, extraction of the leaf using ethanol reduced the levels of these amino acids but not below the recommended WHO standard levels for most of the essential amino acids. Irvingia gabonensis O’Rorke Baill leaf is therefore a potential source of key nutrients.